Amine metabolites in the cerebrospinal fluid in Huntington's chorea. Issue 4 (August 1972) - Curzon, G.; Gumpert, John; Sharpe, David
Abstract : The amine metabolites HVA and 5-HIAA in the lumbar CSF of 15 patients with Huntington's chorea were determined. A negative correlation was found between the severity of symptoms and the CSF HVA, but not 5-HIAA levels. The mean HVA concentration was lower than that of a group of patients with miscellaneous neurological disorders, similar to that of a group with miscellaneous psychiatric disorders and higher than that of a group with Parkinson's disease. The mean 5-HIAA concentration was similar to that of the neurological group and higher than those of the groups with psychiatric disorders or Parkinson's disease. CSF HVA and 5-HIAA concentrations of a single patient with severe akinetic rigid Huntington's chorea were similar to those found in Parkinson's disease. The findings are discussed in relation to previous neuropathological observations and to reported effects of drugs on the choreic symptoms.